Response competition better explains Stroop interference than does response exclusion - Roelofs, Ardi (Psychon Bull Rev, 2020)
Researchers debate whether Stroop interference from an incongruent word in color-naming response time is caused by response competition or by response exclusion. According to the former account, the interference reflects competition in lexical response selection during color name planning, whereas according to the latter, the interference reflects the removal of a motor program for the incongruent word from an articulatory buffer after planning. Here, numerical predictions about the magnitude of Stroop interference as a function of stimulus onset asynchrony were derived from these accounts. These predictions were then tested on representative data in the literature. Measures of goodness-of-fit showed that the numerical predictions of a response competition account are closer to the empirical data than those of the response exclusion account. These results indicate that response competition provides a better explanation of interference in naming than does response exclusion.